PENGARUH PERUBAHAN JUMLAH SUDU TURBIN TURGO TERHADAP DAYA OUTPUT PADA PROTOTYPE PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) - Pandwa Putra, Ida Bagus Made; Arta Wijaya, I Wayan; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM; Vol 9 No 3 (2022): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2022.v09.i03.p1, 2022)
The increase in demand for electrical energy in Indonesia causes a reduction in conventional fuel reserves. This situation forces people to look for alternative energy sources or commonly called new and renewable energy (RE). Seeing the geographical condition of the environment in Indonesia which has the potential for the development of electrical energy by utilizing the flow of water, it is called a Micro Hydro Power Plant (PLTMH). In implementing MHP, one type of impulse turbine can be used, namely the Turgo turbine. This study focused on knowing the effect of variations in the number of blades on a turgo turbine on rotational speed, torque, voltage, current and power produced by PLTMH using a Turgo turbine, with variations in the number of blades used, namely 18,16,14,9,8, and 7 blades. The method used in this research is quantitative experimental, all combinations of parameters tested get the result that the highest output characteristic value occurs using a runner with a number of 18 blades, where the voltage, current, and output power are 8.30 Volts, 0, 88 Ampere, and 7.27 Watt. The fastest turbine rotation results are 782.8 rpm before being connected to a generator and 565.4 rpm after being connected to a generator, while the generator rotation results are 1062.4 rpm. The highest torque produced is 0.1Nm, the maximum efficiency obtained at the runner blade variation is 18 blades, which is 1.1%.